Factors Associated with Hyperbilirubinemia in Newborns at Tanjungpura University Hospital, Pontianak - Anggita Ria Panjaitan; Sri Tumpuk; Emilda Sari; Mohd Yunus (MEDICA (International Medical Scientific Journal), 2025)
In Indonesia, neonatal death is often caused by low birth weight, asphyxia, birth trauma, hyperbilirubinemia, infections, and congenital abnormalities. Hyperbilirubinemia in neonates generally occurs due to the immaturity of organs in processing bilirubin, with phototherapy as the primary treatment. Recent studies have shown an increase in cases of hyperbilirubinemia at Tanjungpura University Hospital in Pontianak, highlighting the need for further research on the factors influencing this condition. The aim of this study is to analyze the factors associated with hyperbilirubinemia in newborns at Tanjungpura University Hospital in Pontianak. This research used an analytical observational design with a cross-sectional approach. The sample consisted of 67 respondents selected through total sampling. The distribution of maternal gestational age showed 49.3% preterm and 50.7% term. Of the respondents, 50.7% had ABO incompatibility, while 49.3% did not. A total of 58.2% of the newborns had normal birth weight, while 41.8% did not. Regarding delivery type, 67.5% were delivered by cesarean section (C-section), and 34.3% by normal delivery. The results of the Chi-Square Continuity Correction test showed p=0.038 for gestational age, p=0.018 for ABO incompatibility, p=0.001 for birth weight, and p=0.202 for delivery type. In conclusion, there is a significant relationship between gestational age, ABO incompatibility, and birth weight with the occurrence of hyperbilirubinemia, but no significant relationship with the type of delivery.